Surgical outcomes of tension-free vaginal tape (TVT)-abbrevo® and TVT-obturator® for the treatment of stress urinary incontinence: a retrospective study - Min Kyeong Kim; Ju Hee Kim; Hee Dong Chae; Jin Ha Chung; Hyeon Ji Kim; Sa Ra Lee; Sung Hoon Kim (Korean Society of Obstetrics and Gynecology, 2021)
Objective We compared the efficacy and postoperative complications of tension-free vaginal tape (TVT)-abbrevo® (TVT-A) and TVT-obturator® (TVT-O) surgeries for the treatment of stress urinary incontinence (SUI). Methods We retrospectively analyzed the medical records of 143 female patients with SUI who underwent TVT-A or TVT-O surgery between January 2010 and December 2019 at the Asan Medical Center in Seoul. We evaluated intra- and postoperative complications such as bladder injury, groin pain, urinary retention, and mesh exposure. We also checked the success rate at 6 months after surgery. Results There were no complications, including fever, hematuria, hematoma of the vulva, or bladder injury, immediately after surgery in either group. Postoperative complications 2 weeks post-surgery were groin pain (11.3%), urinary retention (4.9%), and mesh exposure (0.7%). Groin pain was not significantly different between the two groups at 2 weeks, 3 months, and 6 months after surgery (TVT-O vs. TVT-A after 2 weeks: 12.5% vs. 10.3%, P=0.791; 3 months: 0.0% vs. 1.4%, P=0.999; and 6 months: 0.0% vs. 0.0%, P=0.999). Over 90% of the patients reported cure or improved symptoms in both groups. In the univariate logistic analysis, the type of TVT (TVT-O or TVT-A) was not associated with the success rate (odds ratio, 3.21; 95% confidence interval, 0.59-17.40; P=0.175). Conclusion TVT-A surgery is comparable with TVT-O in terms of high success rate and low frequency of complications, including bladder injury and groin pain.